2005
DOI: 10.1161/01.str.0000177517.01203.eb
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Plasminogen Activator Promotes Matrix Metalloproteinase-9 Upregulation After Focal Cerebral Ischemia

Abstract: Background and Purpose-Thrombolytic therapy with tissue plasminogen activator (tPA) in ischemic stroke is limited by increased risks of cerebral hemorrhage and brain injury. In part, these phenomena may be related to neurovascular proteolysis mediated by matrix metalloproteinases (MMPs). Here, we used a combination of pharmacological and genetic approaches to show that tPA promotes MMP-9 levels in stroke in vivo. Methods-In the first experiment, spontaneously hypertensive rats were subjected to 3 hours of tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
169
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(176 citation statements)
references
References 37 publications
5
169
0
1
Order By: Relevance
“…MMPs are rapidly upregulated after brain injury after trauma, ischemia, and hemorrhage (Mun-Bryce and Rosenberg, 1998;Gasche et al, 1999;Heo et al, 1999;Wang et al, 2000;Power et al, 2003). Degradation of neurovascular substrates lead to blood-brain barrier leakage, edema, and hemorrhage (Asahi et al, , 2001Lo et al, 2004;Tsuji et al, 2005). Furthermore, interruption of cell-matrix signaling may also trigger anoikis-like processes of brain cell death (Gu et al, 2002;Lee and Lo, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are rapidly upregulated after brain injury after trauma, ischemia, and hemorrhage (Mun-Bryce and Rosenberg, 1998;Gasche et al, 1999;Heo et al, 1999;Wang et al, 2000;Power et al, 2003). Degradation of neurovascular substrates lead to blood-brain barrier leakage, edema, and hemorrhage (Asahi et al, , 2001Lo et al, 2004;Tsuji et al, 2005). Furthermore, interruption of cell-matrix signaling may also trigger anoikis-like processes of brain cell death (Gu et al, 2002;Lee and Lo, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…36 LRP can also upregulate matrix metalloproteinase-9, a mediator of extracellular proteolysis of the neurovascular matrix. 37,38 In comparison to the observations by Kassner et al, 24 we examined a larger study population consisting of both patients with and without rtPA treatment. Moreover, this study examined the use of PCT, which has several advantages over perfusion-weighted MR imaging (PWI) in stroke evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms of t-PA-induced blood-brain barrier damage following cerebral ischemia remain poorly understood. Some authors speculate t-PA upregulates brain matrix metallopro-teinase-9 (MMP-9) levels in stroke Wang et al, 2003;Tsuji et al, 2005), resulting in increased vascular permeability. To the contrary, others found that a plasminogen and MMP-9 had an independent mechanism of blood-brain barrier damage through t-PA (Yepes et al, 2003).…”
Section: Discussionmentioning
confidence: 99%